2011
DOI: 10.1136/hrt.2010.208900
|View full text |Cite
|
Sign up to set email alerts
|

Differential right ventricular regional function and the effect of pulmonary hypertension: three-dimensional echo study

Abstract: The right ventricle has distinct features for the inflow, apical and outflow tract compartments, with different extent of contribution to the overall systolic function. In PAH, the right ventricle becomes one dyssynchronous compartment, which itself may have perpetual effect on overall cardiac dysfunction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
48
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(50 citation statements)
references
References 27 publications
2
48
0
Order By: Relevance
“…These "flow poor" characteristics of the apical region support recent 3-D echo findings (3). Calcutteea et al (3) observed that the apical region of the RV chamber contributed less to overall RV contraction than the inflow and outflow regions and proposed that the RV apex could have an important role in maintaining the RV intracavitary circulation other than contraction. The present 4-D flow data suggest that the Residual Volume outlines the functional periphery of the RV chamber, in particular the apical region, and provide a fluid-fluid interface that influences the routes of the other more exchanging flow components.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These "flow poor" characteristics of the apical region support recent 3-D echo findings (3). Calcutteea et al (3) observed that the apical region of the RV chamber contributed less to overall RV contraction than the inflow and outflow regions and proposed that the RV apex could have an important role in maintaining the RV intracavitary circulation other than contraction. The present 4-D flow data suggest that the Residual Volume outlines the functional periphery of the RV chamber, in particular the apical region, and provide a fluid-fluid interface that influences the routes of the other more exchanging flow components.…”
Section: Discussionmentioning
confidence: 99%
“…Scan parameters included the following: VENC ϭ 100 cm/s, flip angle ϭ 8°, echo time ϭ 3.7 ms, repetition time ϭ 6.3 ms, receiver bandwidth ϭ 334 Hz/pixel, parallel imaging (SENSE) speed-up factor ϭ 2, and k-space segmentation factor ϭ 2. The acquired temporal resolution was 49.2 ms, and the spatial resolution was 3 ϫ 3 ϫ 3 mm 3 . The field-of-view (230 ϫ 230 -274 ϫ 274 mm 2 ) and slab thickness (84 -114 mm) were adjusted for each subject to cover both ventricles.…”
Section: Methodsmentioning
confidence: 99%
“…The flow path from RV inflow to outflow followed a gradual curvature through the basal and middle parts of the ventricle, reflecting the RV anatomy with separated inflow and outflow tracts. The apical region was found to not participate as much in flow exchange, supporting previous 3D echocardiographic findings observing that the apical region of the RV contributed less to overall RV contraction than the inflow and outflow regions (151). The visualizations in Paper I suggest that the Residual volume outlines the functional periphery of the RV, in particular the apical region, providing a fluid-fluid interface that influences the routes of the other more exchanging flow components, potentially facilitating the smooth redirection of inflowing blood towards the outflow tract while preserving its KE (152).…”
Section: Physiological Considerationssupporting
confidence: 75%
“…33 Although the effects of chronic pressure overload are most obviously seen in the RV, mechanical dyssynchrony leads to biventricular dysfunction and LV remodeling. The presence of elevated RV pressures leads to dyssynchronous ventricular contraction and leftward ventricular septal bowing, which has been characterized by 2D and 3D echocardiography, 28 speckle-tracking echocardiography, 34 TDI, 35 and MRI. 36 Interventricular dyssynchrony may be the result of delayed activation in regions of the RV due to intraventricular conduction disturbances via mechanisms reviewed above.…”
Section: Interventricular Dyssynchrony and Ventricular Interdependencementioning
confidence: 99%